Comparative analysis of stress responses in C. albicans and C. dubliniensis - Vaughan, Claire (Trinity College (Dublin, Ireland). School of Dental Science, 2006)
Candida dubliniensis is apathogenic yeast that was first identified as a novel species in 1995. It is phylogenetically very closely related to C. albicans. However, despite the close relationship between the two species, C. dubliniensis is significantly less pathogenic. Candida dubliniensis, unlike C. albicans, grows poorly or not at all at temperatures greater then 42°C and when the thermoprotectant disaccharide trehalose is the only available source of carbon. In order to investigate whether the decreased ability of C. dubliniensis to tolerate environmental stresses might contribute to the difference in virulence between the two species the phenotypic and molecular responses of C. albicans and C. dubliniensis to thermal, osmotic and oxidative stress was compared. Growth of representative isolates of the two species in liquid media at temperatures ranging between 30°C-44°C, and with NaCl concentrations ranging between 0.6 M-1.6 M was examined. The results confinned that C. albicans strains SC5314 and 132A have a significantly shorter mean doubling time than C dubliniensis strains CD36, CD539, CD514 and p7718 at temperatures >42°C (F<0.04). The lower survival rates of C. dubliniensis and heat sensitive phenotype observed on agar spot plates further confirmed this data. Similarly, C. dubliniensis, unlike C. albicans, grows relatively poorly in media containing 0.8 M-1.6 M NaCl as determined by the observed differences in doubling times, survival and spot plate assays. In addition hydrogen peroxide viability and spot plate assays confirmed the increased sensitivity of C. dubliniensis to hydrogen peroxide compared to C. albicans.
Keywords: Dental Science, Ph.D.; Ph.D. Trinity College Dublin